Influence of foliar urea with N-(n-butyl) thiophosphoric triamide and planting density on yield and quality of pineapple - Haque, Mohammad Amdadul (2022)
Pineapple (Ananas comosus L.) is one of the most important commercial fruit crops, not only appreciated for its flavour, higher amount of juice, and flesh texture, but also its elevated vitamin C, carotenoids, and high fibre. Nitrogen is an important contributor to the growth, yield, and quality of pineapple, and its loss can be reduced through a split application of foliar urea with N-(n-butyl) thiophosphoric triamide urease inhibitor. Besides N nutrition, planting density also influences the growth, yield, and quality of fruit. Considering the above information, combined efforts have been undertaken to observe nitrogen (N) metabolism, growth, yield, nitrogen use efficiency (NUE), and quality of pineapple with the application of NBPT-treated foliar urea and planting density. The 1st and 2nd experiments were conducted in a greenhouse with 1% (w/v) foliar urea with or without NBPT. Treatments were applied once at 4 months after planting (MAP) in the late afternoon for the 1st experiment to observe the effect of NBPT on the N metabolism of pineapple, while treatments were applied 12 times (starting from 1 MAP, once every month) in 2nd experiment to observe the effect of foliar N with NBPT on growth, yield and quality of pineapple. In 3rd experiment, foliar fertilizer (121 kg each of N and P2O5 including 106 kg K2O) with or without NBPT was applied at different planting densities (43,900; 65,900; and 87,900 plants ha-1) to observe their effect on growth, yield, and quality of pineapple. The 4th experiment was designed to observe the effect of split (6,12 and 24) and dose of N (121 kg ha-1 with or without NBPT, 97 kg ha-1 with NBPT) on the growth, yield, and quality of pineapple. A clear inhibition (74%) of the urease enzyme activity was observed in the pineapple leaf on day 1 due to the function of NBPT at NLU treatment. A higher amount of urea (525 μg g-1 fresh weight at day 3) and a lower amount of NH4+ (79 μg g-1 dry weight at day 1) in the leaf was evidence of hydrolysis inhibition by NBPT. Consequently, the contents of the amino acid (349.60, 341.86, 320.42, 334.43, and 419.30 ng g-1 FW) and protein (4.95, 4.55, 4.59, 4.56, and 4.68 mg g-1 FW) at 2, 4, 6, 8 and 10 days after treatment, respectively were diminished upon NBPT treatment, which demonstrated a change in N metabolism. Foliar application of NLU resulted in more leaf area (3523.55 cm2 plant-1), greater yield (109.82 t ha-1), with higher total soluble solids (13.75%) and NUE (368.43 kg kg-1). The highest planting density (87,900 plants ha-1) resulted in the highest fruit yield (122.84 t ha-1) and NUE (403.12 kg kg-1), while the lowest planting density (43,900 plants ha-1) leads to the highest TSS (13.86%) and sugar content (73.73 mg g-1FW) of MD2 pineapple. Higher N (121 kg ha-1) dose with NBPT performed better in respect of all traits compared to other treatments. However, under 20% reduced dose of N (97 kg ha-1) with NBPT and a higher dose of N (121 kg ha-1) without NBPT were mostly similar in terms of yield (66.32 t ha-1 and 66.98 t ha-1, respectively) and fruit quality (13.68% Brix and 13.88% Brix, respectively) indicating that use of NBPT with urea can save 20% N fertilizer. For split application, the highest (24) number of splits produced heavier fruit (1.60 kg) with a greater yield (70.45 t ha-1) and superior quality considering TSS (14.80%) which was most similar (1.57 kg, 69.06 t ha-1, 14.10%, respectively) with moderate (12) number of splits. This research has led us to conclude that NBPT can be considered as a potential urease inhibitor to slow down urea hydrolysis that positively influences N metabolism, growth, yield, NUE, and quality of pineapple. This study also intimates that a higher yield can be obtained from high-density planting. Moreover, better yield with superior quality fruit can be able to harvest from higher N with more split. However, NBPT has great potential to save about 20% of N fertilizer.